NUTRIENT AND BIOACTIVE SUBSTANCE CONTENTS OF EDIBLE PLANTS GROWN NATURALLY IN SALIPAZARI (SAMSUN) - Demir, Esra; Turfan, Nezahat; Ozer, Harun; Ustun, Nebahat Sule; Peksen, Aysun (Uniwersytet Przyrodniczy w Lublinie, 2020)
This study was carried out for the determination of nutrient and bioactive substance contents of edible wild plants consumed as vegetables in Samsun's Salıpazarı district during September 2014 and August 2016 period. In the selected villages from identified locations, 11 species that naturally grow and are consumed as vegetables such as Alcea apterocarpa Boiss., Rumex crispus L., Urtica dioica L., Trachystemon orientalis L., Oenanthe pimpinelloides L., Smilax excelsa L., Capsella bursa-pastoris L., Aegopodium podagraria L., Arum italicum Miller, Ornithogalum sigmoideum Freyn et. Sint. and Amaranthus retroflexus L. have been identified. Protein, proline, free amino acid, superoxide dismutase (SOD) activity, lipid peroxidation level (MDA), glucose, sucrose, total soluble carbohydrate, chlorophyll, total carotenoids, β-carotene, lycopene, flavonoids, and anthocyanins contents of these plants were determined as 32.79–106.40 mg/g dry weight (DW), 5.71–47.66 µmol/g DW, 29.62–61.75 µg/g DW, 82.75–240.06 IU/mg protein, 106.36–531.05 µmol/g DW, 31.96–87.24 mg/100 g DW, 10.97–25.49 mg/100 g DW, 174.3–422.2 mg/100 g DW, 7.79–25.96 mg/100 g DW, 102.01–436.93 µg/100 g DW, 115.86–459.64 µg/100 g DW, 6.38–30.28 mg/100 g DW and 10.17–21.52 mg/100 g DW, respectively. As a result of the analyses, it was determined that there were signiﬁcant differences (P < 0.01) in terms of all parameters examined among species.
Keywords: Science; Q; carotenoids; Plant culture; nutritional; QD415-436; Biochemistry; SB1-1110; beta-carotene; β-carotene; edible wild herbs; protein; 2. Zero hunger; 15. Life on land; 6. Clean water